A TRANSISI LAYANAN KAJI ETIK PENELITIAN di ERA DIGITAL - Mrs. Tri; Pratiwi Wulandari; Diana Nurrohima; Yasinta Nofia; Erindra Cahyanto; Usman Sudarmadji (Sekolah Tinggi Ilmu Kesehatan Estu Utomo Boyolali, 2022)
Research is a way of advancing science and technology to improve human benefit. Every research plan involving humans and experimental animals must be reviewed ethically to maintain the dignity of the subject. Ethics review services by the research ethics committee have changed from time to time in line with the development of science and information technology. To determine the quality of service, it is necessary to evaluate the level of satisfaction of ethical service users for both researchers and reviewers. This study uses a descriptive survey method on researchers and reviewers involved in the ethical feasibility of KEPK FK UNS. Data analysis with quantitative descriptive. The results showed that 89.69% of the 59 researchers and 89.56% of the 14 reviewers agreed that the KEPK FK UNS ethics service was good. The percentage of researcher satisfaction shows 35.59% very satisfied, 37.29% satisfied, and 27.12% quite satisfied. The satisfaction level of the reviewers was 28.57% very satisfied, 42.86% satisfied, and 28.57% quite satisfied. This research concludes that the ethical service of KEPK FK UNS is considered good and satisfactory by researchers and reviewers. Keywords: Ethical Clearance, Ethical Feasibility, Research Ethics Commission, Level Of Satisfaction ABSTRAK Penelitian merupakan cara memajukan ilmu pengetahuan dan teknologi untuk meningkatkan kemaslahatan manusia. Setiap rencana penelitian yang melibatkan manusia dan hewan coba harus dilakukan kaji etik guna menjaga kemuliaan subjek. Pelayanan kaji etik oleh komite etik penelitian, mengalami perubahan dari waktu ke waktu seiring dengan perkembangan ilmu pengetahuan dan teknologi informasi. Untuk mengetahui kualitas layanan, perlu dilakukan evaluasi tingkat kepuasan pengguna layanan etik baik bagi peneliti maupun penelaah. Penelitian ini menggunakan metode deskriptif survei pada peneliti dan penelaah yang terlibat dalam kelaikan etik KEPK FK UNS. Analisis data dengan deskriptif kuantitatif. Hasil penelitian menunjukkan 89,69% dari 59 peneliti dan 89,56% dari 14 penelaah setuju layanan etik KEPK FK UNS sudah baik. Persentase kepuasan peneliti menunjukkan 35.59% sangat puas, 37.29% puas dan 27,12% cukup puas. Tingkat kepuasan pada penelaah diperoleh 28.57% sangat puas, 42.86% puas dan 28.57% cukup puas. Kesimpulan penelititian ini yaitu pelayanan etik KEPK FK UNS dinilai sudah baik dan memuaskan oleh peneliti dan penelaah. Kata kunci: Izin Etik, Kelaikan Etik, Komisi Etik Penelitian, Tingkat Kepuasan